Analyzing Chromosomes - Czepulkowski, B. H (BIOS Scientific, 2001)
A guide to cytogenetic techniques. It covers culture of human cells for chromosomal analysis, staining and banding of chromosome slides, types of abnormalities observed in chromosomes, constitutional chromosome abnormalities, and acquired chromosome abnormalities in malignancy.